Pengaruh Video Pembelajaran terhadap Hasil Belajar Dasar-dasar Teknik Elektronika di Sekolah Menengah Kejuruan - Rivaldi Rahman; Hambali Hambali (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2021)
This study aims to analyze the effect of the use of instructional video on student learning outcomes in Class X on the subjects of the Basics of Electronic Engineering with learning material is Active and Passive Electronic Components. The research was conducted at SMK Negeri 1 Pariaman. Data was collected using a research instrument that given post-test in the form of multiple-choice questions to the student with the odd absent numbers as experiment class is X TOI group A and the student with the even absent number as the control class is X TOI group B. hypothesis was carried out using T-test analysis, the T-test is used to analyze the difference on students learning outcomes that use learning media in the form of text in Microsoft Word and other students that use learning media in the form of learning video. The results of the hypothesis test show that the use of instructional video has a significant effect on student learning outcomes and shows that there is an influence significant difference between the post-test results of the experimental class that uses instructional video and the control class that does not use instructional videos in the Basics of Electronic Engineering Class X TOI at SMK Negeri 1 Pariaman.